THE FUNCTIONS OF HEDGES IN THE CONCLUSION SECTION OF THESES WRITTEN BY THE INDONESIAN EFL STUDENTS - Elok Widiyati (Faculty of Humanities, Universitas Jenderal Soedirman, 2015)
This article provides the explanation about how hedges function in the conclusion section based on Hyland’s hedges functions (1996). This study belongs to descriptive qualitative. The data sources of the study were conclusion sections of theses in English written in the year of 2000 to 2010. Based on the analysis of hedges function proposed by Hyland, the Indonesian EFL students mostly used hedges as writer-oriented hedges, 37 %. It seems that the students could not minimize mistake upon statement in the proposition, could not show less absolute statement, and also could not convey arguments or statements speculatively. English lecturers should take hedges as one of the learning materials so that the students will be familiar in applying them for the academic writings. Moreover, I think that hedges studies provide assistance for the students in employing hedges appropriately.